1995
DOI: 10.1007/bf02053857
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate colitis

Abstract: At a mean of nearly five years after surgery, failure appears to occur more frequently in patients with indeterminate colitis than in patients with chronic ulcerative colitis. However, the great majority of indeterminate colitis patients (> 80 percent) have long-term functional results identical to those of patients with chronic ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Thus, a total of 27 patients (21.6%) had an unfavourable result, whereas 78.4% were satisfied. The results of other published series differ considerably, with failure rates from 3.4% in the best reports to 8–11% in others [6, 7, 19]. Failure rates in these reports refer to the removal or defunctioning of the reservoirs.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, a total of 27 patients (21.6%) had an unfavourable result, whereas 78.4% were satisfied. The results of other published series differ considerably, with failure rates from 3.4% in the best reports to 8–11% in others [6, 7, 19]. Failure rates in these reports refer to the removal or defunctioning of the reservoirs.…”
Section: Discussionmentioning
confidence: 92%
“…The Cleveland Clinic reported a pouch failure rate of 3.4%, which is a low rate compared to other large series with failure rates of 8%–11% [4, 5]. They suggest that careful selection of patients and attention to surgical details and postoperative followup, as well as the frequent use of double-stapled IPAA may cause their good results [29].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively accurate diagnosis of IBDU can be of great use in the selection of surgical procedures like IPAA. Earlier studies have shown that compared with UC patients, IBDU patients with IPAA showed a higher rate of pouch failure and complications [ 26 29 ]. Conversely, in recent studies, the long-term functional outcome and pouch failure rate of CD or IBDU patients were identical to those of UC.…”
Section: Discussionmentioning
confidence: 99%